Strategic Attributes and Organizational Performance: Toward an Understanding of the Mechanism Applied to the Banking Sector - Tang, Honglei; Rasool, Zeeshan; Sarmad, Muhammad; Ahmed, Ammar; Ahmed, Umair (Frontiers in Psychology, 2022)
The study examines and theorizes the importance of strategic attribute constructs (strategic orientation, organizational culture, and organizational internal market orientation) as applied to Pakistan’s banking sector by identifying their roles in enhancing organizational performance, along with a mediating effect of organizational commitment. The current study adopted quantitative research designs and methods to determine structural relationships between the proposed constructs. A totoal of ten hypotheses were tested underpinned by the Resource-Based View of the Firm and Social Exchange theories. The strategic attributes studied were significantly and positively related to, and enhance, organizational performance if the banks: (1) focus on strategic positioning, (2) nurture a strong organizational culture, (3) strategize internal marketing practices, and (4) boost organizational commitment. The findings supported the mediating role of organizational commitment between the strategic attributes and organizational performance. The scope was limited to six large Pakistani banks in five major cities, and the results should not be generalized to other business sectors or to small-to-mid-sized banks inside, or outside, of Pakistan. This study contributes to existing literature and supports prior research while filling in gaps in the literature concerning developing countries.